Working Capital Management: A Policy for Company Performance - Diah, Widyanti; Puspita, Nolla (Universitas Batam, 2024)
The aim of this research is to analyze the influence of working capital management components on profitability as measured by ROA (return on assets). The components of working capital management in this research include account receivable period, account payable period, inventory period, cash conversion cycle, firm size, sales growth, leverage, gross working capital turnover, current assets to total assets, and current liabilities to total assets. The research subjects were companies listed on the Indonesia Stock Exchange in 2017-2021. Through purposive sampling, 67 companies were selected that met the requirements, a total of 335 observation data. The research results show that the cash conversion cycle and leverage have a significant negative influence on company profitability, while company size has a significant positive influence on profitability in listed companies in Indonesia. This research also shows that that account receivable period, account payable period, inventory period, sales growth, gross working capital turnover, current assets to total assets, and current liabilities to total assets do not have a significant influence on company profitability on the Indonesia Stock Exchange